THE PREREQUISITES FOR ENTREPRENEURIAL UNIVERSITIES FORMATION IN UKRAINE - Maryna, Salun; I., Lutskyi Andrii; Myroslav I, Lutskyi; Roman V, Zvarych; Kateryna, 5Zaslavska; Oksana, Tsukan (International Journal of Psychosocial Rehabilitation, 2020)
Universities of a new generation need to unite the representatives of science and business who are interested in turning ideas into a real market product. This paper provides an original analysis of prerequisites for the formation and development of entrepreneurial universities in Ukraine. This study used the results of the generalization of literature on entrepreneurial universities and European experience on their formation. It has shown the main approaches to the understanding of the nature and features of entrepreneurial universities and underlines its global impact. Analysis of the results of research has allowed to formulate the author’s definition of “entrepreneurial university” and to form a synthesis of the key judgments about entrepreneurial universities. It was concluded that the key focus in determining of the entrepreneurial university must be made on the results of the commercialization of research activities of universities, as well as the practical training of students up to the demand of business. Statistical data and international ranking reports were used to illustrate the current state of the higher education system of Ukraine. Peculiarities of the educational environment in the context of global changes and the identified trends in world studies were considered. The constraints faced by the educational system of Ukraine were allocated, including legislation base, the autonomy of universities issues, the diversification of funding sources. This leads to the conclusion that the use of European experience will allow adapting the educational space of Ukraine to the requirements of time and the global labour market. The functioning of higher education system became the basis for the substantiation of prerequisites of the establishing of entrepreneurial universities in Ukraine, defining the catalysts factors of entrepreneurial activity of universities and identifying barriers to their development.